543. SARS-CoV-2 Viral Dynamics For Symptomatic People Living with HIV Requiring Hospitalization For COVID-19. (31st December 2020) - Virata, Michael D; Villanueva, Merceditas; Shenoi, Sheela; Ladines-Lim, Joseph B; Aoun-Barakat, Lydia
Abstract: Background: Over 8 million people have been infected with severe acute respiratory syndrome 2 (SARS-CoV-2). People living with HIV (PWH) affected by SARS-CoV-2 represent a small proportion of patients admitted to the hospital for COVID-19 disease. Viral dynamics in this subpopulation are still unknown. Methods: We conducted a retrospective cohort study from a large, urban academic center in New Haven, CT of patients consecutively admitted with laboratory confirmed SARS-CoV-2 infection through May 31, 2020. Main outcome measure was the ribonucleic acid (RNA) viral load (VL) detected in respiratory samples by cycle threshold (Ct) values and trend over time as a measure of nucleic acid concentration and replication. Epidemiological, clinical, laboratory results, ART treatment, COVID treatment and outcomes were abstracted from patient records. We evaluated the relationship between virologic data and disease severity. Results: Among 19 PWH hospitalized with covid19, 84% were > 50 years of age, 53% were women, 63% were black, 95% were on antiretrovirals, 95% with undetectable HIV VL (< 50 copies/ml), and median CD4 count of 827.9 cells/mm3. Symptom duration was 2–14 days. Median length of stay was 12 days. There was no in-hospital mortality. A total of 62 respiratory samples were collected at various time points and evaluated for SARS-CoV-2 RNA viral load. Eight patients had 1 specimen. Patient with more severe disease had higher baseline SARS-CoV-2 viral loads. Mean Ct values for N1 and N2 on admission were 21.6 and 23.7, respectively. Conclusion: PWH with COVID19 represents only a small percentage of hospitalized patients and viral dynamics are not well defined. SARS-CoV-2 VL was higher among PWH with advanced disease at the presentation of illness. Overall, PWH with COVID-19 had favorable outcomes. Disclosures: All Authors : No reported disclosures